Analysis Effect Of Management Skills Finance, Budgeting, Accuracy Of Financial Characteristics Of Cooperative City Surakarta - Jumingan, Jumingan; Isstianto, Sunarto (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
Cooperative as a container or agencies that handle economic activity is said to be the cornerstone of the cooperative economy capable of creating wealth and prosperity. The rapid growth of cooperatives can be seen from the economic feasibility of their business, it can be said that a healthy cooperative effort, if the sources of capital that has been used and exploited by its members in accordance with the goals and objectives of the cooperative, and efficient cost control management in order to serve the needs of members effectively.The issues raised in this study about how to manage finances, penyusunanan budget, how close watch timeliness of financial statements and its financial ratios of the characteristic koperasi.Adapun cooperative goal to go into detail in a healthy and cooperative economy is a joint research masyarakat.Kontribusi is to add insight and wisdom cooperative managers, able to take into account their own tax planning, enhance trust a third party. In connection with this study keresponden direct the analysis tools used are: classical assumption test validity, reliability testing, lenier multiple regression analysis, hypothesis testing using t-test and F test The findings of this study is lacking in attention to financial management, efficient, effective, quick, and reliable transfaran, ignore the timeliness of financial reporting, lacking in account all aspects of finance and financial ratios related to liability, lack of understanding of the growth and health cooperatives. The advice can be given is this study is the manager or managers should pay attention to guidance from the local cooperatives and related offices, often participate in training/education workshops to broaden the decision-making.